Desain Program Tahunan Dan Program Semester - Dina Latifah; Assyra Andini Manday; Anggita Cahyani; Alfina Fadhia; Ahmad Prayogi (Journal of International Multidisciplinary Research, 2024)
Prota (Annual Program) and Promes (Semester Program) are important documents in the world of Indonesian education. They are structured learning plans that guide teachers in carrying out teaching and learning activities during the school year. This article aims to understand and describe the design of annual programs and semester programs, apart from that, this article can be a reference for teachers in creating annual programs and semester programs. This research uses the library research method, namely by reviewing various literature related to Prota and Promes, such as books, scientific journals and online articles. A good Prota and Promes design must contain several important elements, including: Learning objectives: Formulate the objectives to be achieved in the learning program. Basic competencies: Determine the basic competencies that will be taught. Time allocation: Determine the time allocation for each basic competency. Learning activities: Designing interesting and effective learning activities. Assessment: Determine the assessment method to be used.